Clinical Characteristics and Short-Term Outcomes of Severe Patients With COVID-19 in Wuhan, China - Feng, Xiaobo; Li, Peiyun; Ma, Liang; Liang, Hang; Lei, Jie; Li, Wenqiang; Wang, Kun; Song, Yu; Li, Shuai; Yang, Wei; Yang, Cao (Frontiers in Medicine, 2020)
Background. A novel pneumonia (COVID-19) which is sweeping the globe was started in December, 2019, in Wuhan, China. Most of the deaths were in severe and critically cases, but information on prognostic risk factors for severe ill patients is incomplete. Further research is urgently needed to guide clinicians, so we prospectively evaluate the clinical outcomes of 114 severe ill patients with COVID-19 for short-term in the Union Hospital in Wuhan, China. Methods. In this single-centered, prospective and observational study, we enrolled 114 severe ill patients with confirmed COVID-19 from Jan 23, 2020 to February 22, 2020. Epidemiological, demographic, laboratory, treatment and outcome data were recorded, and the risk factors for poor outcome was analyzed. Results. Among enrolled 114 patients, 94 (82.5%) patients were classified as good outcome group, average age of 63.96 ± 13.41 years, Common clinical manifestations included fever, cough, and fatigue. Compared with good outcome group, poor outcome group more frequently had lymphopenia, and lower albumin, partial arterial oxygen pressure and with higher levels of lactate dehydrogenase, creatine kinase, hypersensitive troponin I, C-reactive protein, ferritin, blood urea nitrogen and D-dimer as well as markedly higher levels of IL-6, IL-10. Absolute numbers of T lymphocytes, CD8 + T cells decreased in almost all the patients, and were markedly lower in poor outcome group than good outcome group. We also found that traditional Chinese medicine can significantly improve the patient's condition, which is conducive to the transformation from severe to mild. In addition, univariate and multivariate Cox analyses of potential factors for poor outcome patients indicated that some factors related to the development of poor outcome. Conclusion. In summary, we firstly reported this single-centered, prospective and observational study for short-term outcome in severe patients with COVID-19. We found that cytokine storm and uncontrolled inflammation responses, liver, kidney, cardiac dysfunction may play important roles in final outcome of severe ill patients with COVID-19. Our study will let clinicians to be benefit to rapidly estimate the likelihood risk of short-term poor outcome for severe patients.